Pembaharuan Pemikiran Islam dan Relevansinya bagi Pengembangan Pendidikan di Indonesia - Happy Susanto (Postgraduate Program Magister Pendidikan Agama Islam, 2018)
The issue of renewal will always be associated with the advancement of science and technology as well as the changing demands of the times. Modernization or renewal can be an attempt to improve the situation both in terms of ways, concepts, and a set of methods commonly applied in order to deliver better circumstances. In the context of renewal education is the absolute thing to be done because part of maintaining the existence of education itself. Islamic education is uniquely different from other types of educational theory and practice largely because of the all-encompassing influence of the Qur’an. The renewal of Islamic education is an attempt to actualize the great values of religion in the form of an empirical and historical life. Nurcholis Madjid and Kuntowijoyo are two great Islamic thinkers of Indonesia who seek to actualize Islamic values in everyday life. Although not specific in the world of education, but what is done in Islamic renewal can be used in renewal in education. The values of religion that are still normative and subjective must be transformed into theories that can be translated in the empirical world and become objective. This paper aims to explore the thinking of Islamic renewal of these two figures and find its relevance to the development of Islamic education.